HUBUNGAN PROMOSI DENGAN KEPUTUSAN PEMBELIAN KAMAR TAMU DI DAIMA HOTEL PADANG - Shabrina, Nova (journal of residu, 2019)
This study aims to determine of promotional relationship with the decision purchase guest rooms in Daima Hotel Padang. This type of research is classified as correlational. The population in this study were guests who stayed monthly at 5.079 people and number of sample in this study amounted to 98 guests who were staying with the sampling technique was incidental sample. The technique of data collection is done using a questionnaire with a Likert scale that has been tested for validity and reliability. Technical analysis using the help of the SPSS Computer Program version 16.00. The results showed: 1) the promotion in Daima Hotel Padang are at an average score of 68.21, 2) the decision purchase guest rooms in Daima Hotel Padang was at an average score of 69.6, 3) The results of Person Product Moment Correlation  indicate that there is a positive (sufficient) and insignificant relationship between the promotion and the purchasing decision assessed by guests staying at daima Hotel Padang, with a correlation coefficient (r) of 0.166 (sig 0.102) with sufficient category because it is in the range > 0 – 0.25. This means that the better the promotion is done, the higher the decision purchase a guest room at Daima Hotel Padang.